Major trends in the study of Malay statecraft since 1900 - Sulkafle, Mohamad Hazizie (IIUM Press, 2024)
This study aims to make a comprehensive survey on the existing literature related to Malay statecraft (ketatanegaraan) and the relevant studies that have been conducted and published in Malaya (then Malaysia) since 1900. Statecraft is related to the legitimacy and the idea and concept of the sovereignty of the ruler as understood and practised within the Malay society. Through this historiographical survey, this study has identified several major trends or approaches adopted by scholars in studying Malay statecraft. Among the trends that have been identified is studying Malay statecraft based on the specific genre of “Mirrors for Princes” literature. This trend was later expanded by studying the elements of statecraft that existed in Malay historical narratives, hikayat (folktale) and legal texts. These scholars have significantly contributed to enrich the materials in this field and were able to establish Malay statecraft studies as a distinguished field of study. Regardless, it has been identified that several aspects need to be improved and focused on by scholars to further widen the scopes and strengthen Malay statecraft studies. Hence, this study calls for the redefinition of scopes and frameworks for Malay statecraft studies to ensure its sustainability and relevancy in the contemporary era.